ANALISIS EFEKTIVITAS DAN EFISIENSI METODE ENCODING DAN DECODING ALGORITMA BASE64 - Mochammad Syahrul Kurniawan; I Gede Ardi Sukaryadi Putra; I Made Agastya Maheswara; Reynaldus Yoseph Maria Neto Labamaking; I Made Edy Listartha; Gede Arna Jude Saskara (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
This study discusses the methods of encoding and decoding the base64 cryptographic algorithm. The term encoding means a process of converting plaintext into ciphertext. While decoding is a term that means the process of turning ciphertext back into plaintext. In general, classical cryptography has been abandoned because of its logic which can be easily solved, so now it has switched to modern cryptography which operates in bit-binary mode which is formed from ASCII code. The base64 algorithm is a form of modern cryptography which is included in the modern type of block cipher cryptography. This study aims to obtain a comparison between 3 types of tools in carrying out a cryptographic encode and decode process on the base64 algorithm. The 3 types of tools include the Base64 Python Program, Bash Base64 Kali Linux, and CyberChef which are online tools. This type of research method uses qualitative methods because it tends to use analysis in research. Where the results of the first comparison are used to make it easier to see the accuracy of the encoding and decoding processes and the results of the second comparison are used to compare in terms of time efficiency when encoding the three tools using 1,000 words which will continue to be added by 4,000 words, up to a total of 9,000 words . These words are taken using dummy text (lorem ipsum).